2013
DOI: 10.1002/macp.201300473
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Branched Polyoxymethylene Synthesized by Cationic Copolymerization of 1,3,5‐Trioxane with 3‐(Alkoxymethyl)‐3‐ethyloxetane

Abstract: Novel branched polyoxymethylene copolymers are synthesized by cationic copolymerization of 1,3,5‐trioxane (TOX) with 3‐(alkoxymethyl)‐3‐ethyloxetane (ROX) using BF3·Et2O as an initiator. Four oxetane derivatives with different side‐chain lengths (from 1 to 6 carbons) are tested for copolymerization. The copolymer composition is controlled by the feed ratio of ROX, and influenced by the chain length of alkyl group on ROX. The incorporation ratio and side‐chain length of the ROX unit have great influence on the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 27 publications
1
6
0
Order By: Relevance
“…In addition, we tested the stability of the formed adhesive layer in water, using the adhesion samples prepared from dry conditions at 60 °C as the examples. After soaking into water at 40 °C for 24 h, similar binding strength was maintained, which indicated that the PVA‐ g ‐DHBA processed good water resistance compared to our previous report …”
Section: Resultssupporting
confidence: 68%
See 1 more Smart Citation
“…In addition, we tested the stability of the formed adhesive layer in water, using the adhesion samples prepared from dry conditions at 60 °C as the examples. After soaking into water at 40 °C for 24 h, similar binding strength was maintained, which indicated that the PVA‐ g ‐DHBA processed good water resistance compared to our previous report …”
Section: Resultssupporting
confidence: 68%
“…After soaking into water at 40 °C for 24 h, similar binding strength was maintained, which indicated that the PVA-g-DHBA processed good water resistance compared to our previous report. [53,54]…”
Section: The Effect Of the Condition Of Adhesion On Bonding Strength mentioning
confidence: 99%
“…Poly (3-ethyl-3-( alkyl )oxymethyloxetane), PCmEO, having an alkyl side chain with various lengths ( m = 1, 2, 4, 6, 8, and 12) was used in this study ( Figure 1 ). PCmEO was synthesized based on previous studies ( Mu et al, 2013 ; Sai et al, 2017a ). The monomers of PCmEO and CmEO were synthesized from the coupling of 3-ethyl-3-hydroxymethyloxetane (EHO) and alkyl compounds modified with leaving groups in the base solution ( Scheme 1 ).…”
Section: Methodsmentioning
confidence: 99%
“…H-nuclear magnetic resonance spectrometry for the samples was conducted by dissolving about 10 mg of the sample in 0.38 mL of 1,1,1,3,3,3-hexafluoro-2-propanol (HFIP) and then by adding 0.12 mL of deuterated chloroform to the solution, [15] using a BRUKER 500 MHz.…”
Section: Instrumentationmentioning
confidence: 99%
“…Figures 7 and 8 show the TGA curves in nitrogen atmosphere for S 5 , S 10 , S 15 , and S 5-R samples and a homopolymer sample (S Homo ) synthesized with the same catalyst. For copolymer samples, a two-step degradation was observed where the first which ended at 230 °C, which could be related to chains with a higher proportion of trioxane [15] (oxymethylene units) and a lower proportion of comonomer (oxyethylene units). To prove the claim, TGA test for the homopolymer synthesized sample with the same catalyst has been shown in Figure 7.…”
Section: (1)mentioning
confidence: 99%